Turkish Balance, or Türkiye’s Foreign Policy Strategy in the Black Sea Region Following the Special Military Operation - Aleksandr A. Irkhin; Olga A. Moskalenko; Natalia E. Demeshko (Vestnik RUDN. International Relations, 2024)
The Black Sea region in its various geopolitical configurations is a zone of priority for the Turkish elite. Prior to the Treaty of Küçük Kaynarca (1774), the Black Sea was regarded as the “Sultan’s harem.” Being essentially a peninsula between the Mediterranean and Black Sea, Türkiye is interested in maintaining control over the Black Sea space or in sharing it with another strong power having access to it. The authors aim to identify and explore Türkiye’s foreign policy strategy in relation to the Black Sea region as one of the key geopolitical spaces for Ankara’s national interests. The foreign policy strategy is understood as a long-term mechanism of the subject in relation to objects and competing subjects, which aims to achieve the most favorable spatial position with the help of military and non-military means and appropriate resources, taking into account the timeliness factor. The article solves specific tasks: it identifies the stable characteristics of Turkish foreign policy, shaped by historical experience and geography, which underlie Ankara’s foreign policy strategy; it shows and studies the strategic vision of the Turkish elite in relation to the Black Sea region; it reveals the mechanisms of influence of external geopolitical subjects on the region and the combination of these mechanisms with Turkish national interests. The concept of Turkish balance is introduced as mechanism of Türkiye’s foreign policy strategy whose main purpose is to integrate stronger powers into the logic and algorithms of foreign policy balances of stronger powers with their mutual opposition and further balancing act, which allows Türkiye to receive maximum geo-economic and geopolitical dividends. The research methodology is represented by systemic, geopolitical and civilizational approaches. Given the role of the Black Sea region in the military-political dynamics since February 2022, the mechanisms of Türkiye’s foreign policy strategy in relation to the region are becoming crucial for Russia in various areas of national security. Authors propagate that February 2022 is the inertia of the events of March 2014 and deeper, of the postponed crisis of 1991 caused by the disintegration of the USSR. However, it was the beginning of the special military operation that brought the military and political confrontation at the global and regional levels into the format of open confrontation. Russia has challenged the West and its system of allies.